ONTOLOGI DALAM APLIKASI KARYA SASTRA “RONGGENG DUKUH PARUK” - Sulmi Magfirah; Puspita Dewi (Humanitatis : Journal of Language and Literature, 2018)
Ronggeng Dukuh Paruk's (RDP) literary work is a part of the work considered in the world because in some countries the literary work is one of the materials studied by students as academic studies. The purpose of this study is to examine the nature of RDP's work by looking at the ontology of the creation of these literary works. This research uses sociology of literature approach by looking at the relation between the literary works with the community context. The results of this study are that the RDP literature illustrates the tense state of political struggle and social conditions at that time. This work also explains the atmosphere of a small village with various community characters full of erotic lifestyles. This is illustrated through the Ronggeng figure namely Srintil and the inner complication of Rasus who hates the inaugural process of Srintil who will become ronggeng. One of the night process of not having mosquito nets is a ritual to become a ronggeng. Auctions of virginity like this occur in the Hamlet of Paruk, the value of sexuality highlighted by Tohari as one of the harsh criticisms that women are more valued and protected. Literary works in the form of novels written by Tohari are not only literary works that can be read and enjoyed, but Tohari emphasizes on moral values that must be imbedded in community.